Synovial fluid from end-stage osteoarthritis induces proliferation and fibrosis of articular chondrocytes via MAPK and RhoGTPase signaling. Issue 6 (June 2022) - Housmans, B.A.C.; Neefjes, M.; Surtel, D.A.M.; Vitík, M.; Cremers, A.; van Rhijn, L.W.; van der Kraan, P.M.; van den Akker, G.G.H.; Welting, T.J.M.
Summary: Objectives: Alterations in the composition of synovial fluid have been associated with adverse effects on cartilage integrity and function. Here, we examined the phenotypic and proliferative behavior of human articular chondrocytes when cultured in vitro for 13 days with synovial fluid derived from end-stage osteoarthritis patients. Materials and methods: Chondrocyte proliferation and phenotypical changes induced by osteoarthritic synovial fluid were analyzed using DNA staining, RT-qPCR, immunostainings, and immunoblotting. The molecular mechanisms by which osteoarthritic synovial fluid induced fibrosis and proliferation were studied using a phospho-protein antibody array and luciferase-based transcription factor activity assays. Specific pathway inhibitors were used to probe the involvement of pathways in fibrosis and proliferation. Results: Prolonged stimulation with osteoarthritic synovial fluid sustained chondrocyte proliferation and induced profound phenotypic changes, favoring a fibrotic over a chondrogenic or hypertrophic phenotype. A clear loss of chondrogenic markers at both the transcriptional and protein level was observed, while expression of several fibrosis-associated markers were upregulated over time. Phospho-kinase analysis revealed activation of MAPK and RhoGTPase signaling pathways by osteoarthritic synovial fluid, which was confirmed by elevated transcriptional activity of Elk-1 and SRF. Inhibitor studies revealed that ERK played a central role in the loss of chondrocyte phenotype, while EGFR and downstream mediators p38, JNK and Rac/Cdc42 were essential for fibrosis-associated collagen expression. Finally, we identified EGF signaling as a key activator of chondrocyte proliferation. Conclusions: Osteoarthritic synovial fluid promoted chondrocyte fibrosis and proliferation through EGF receptor activation and downstream MAPK and RhoGTPase signaling.